Sporting Faith: Exploring Displays of Faith as Part of Christian Higher Education Athletic Program Identity - Laci McRee; Jason W. Lee; Dawn Tolbert (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2022)
Contemporary higher education is made of a marketplace where institutions aggressively market themselves to student consumers who “shop” for school options (Tolbert, 2014). This study examines the marketing of faith-based higher education institutions’ athletic programs to determine how faith-related missions are revealed on institutional websites. Higher education institutions analyzed in this study consisted of 112 of the 141 member institutions that are members of the Council for Christian Colleges & Universities (CCCU), which compete in sanctioned intercollegiate athletics programs (e.g., NCAA, NAIA, NCCAA). The study attempted to quantify how strongly a university’s athletic program portrays the faith dimension of the school’s identity through the visual marketing tool of the athletic departments’ website to determine whether that measure is indicative of external perception. For this study, institutional websites were examined to measure the strength of faith identity presented on the sites using a content analysis of the university tagline, university mission statement, and athletic department mission statement. Faith expression was lacking in 53% of taglines and 33% of athletic department mission statements. Study results reflect that CCCU member institutions should streamline the faith expression of the university mission statement into the message conveyed in the tagline and the athletic department mission statement.
Keywords: Christianity; Faith; Branding; Identity; Higher Education